Deterministic arterial input function selection in DCE-MRI for automation of quantitative perfusion calculation of colorectal cancer - Tönnes, Christian; Janssen, Sonja; Golla, Alena-Kathrin; Uhrig, Tanja; Chung, Khanlian; Schad, Lothar R.; Zöllner, Frank G. (Magnetic resonance imaging, 2021)
Development of a deterministic algorithm for automated detection of the Arterial Input Function (AIF) in DCE-MRI of colorectal cancer. Using a filter pipeline to determine the AIF region of interest. Comparison to algorithms from literature with mean squared error and quantitative perfusion parameter Ktrans. The AIF found by our algorithm has a lower mean squared error (0.0022±0.0021) in reference to the manual annotation than comparable algorithms. The error of Ktrans (21.52±17.2%) is lower than that of other algorithms. Our algorithm generates reproducible results and thus supports a robust and comparable perfusion analysis.
Gesehen am 23.04.2021